Self-Reported Risk and Delinquent Behavior and Problem Behavioral Intention in Hong Kong Adolescents: The Role of Moral Competence and Spirituality - Shek, Daniel T. L.; Zhu, Xiaoqin (Frontiers in Psychology, 2018)
Based on the six-wave data collected from Grade 7 to Grade 12 students (N = 3,328 at Wave 1), this pioneer study examined the development of problem behaviors (risk and delinquent behavior and problem behavioral intention) and the predictors (moral competence and spirituality) among adolescents in Hong Kong. Individual growth curve models revealed that while risk and delinquent behavior accelerated and then slowed down in the high school years, adolescent problem behavioral intention slightly accelerated over time. After controlling the background socio-demographic factors, moral competence and spirituality were negatively associated with risk and delinquent behavior as well as problem behavioral intention across all waves as predicted. Regarding the rate of change in the outcome measures, while the initial level of spirituality was positively linked to the growth rate of risk and delinquent behavior, the initial level of moral competence was negatively associated with the growth rate of problem behavioral intention. The theoretical and practical implications of the present findings are discussed with reference to the role of moral competence and spirituality in the development of adolescent problem behavior.